2020
DOI: 10.17221/55/2020-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bacteriophages of the Staphylococcus aureus variant bovis

Abstract: Bacteriophages may be an alternative method of treatment for antibiotic-resistant bacteria, including mastitis in cows. Our study describes the initial isolation and bacteriological activity of bacteriophages, circulating on dairy farms, the against S. aureus var. bovis. Samples of cow’s milk secretions with signs of mastitis and sewage water were used as the study material. The isolation and production of pure bacteriophage lines were performed according to the double agar method. The method of studying a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Those antibiotics were chosen depending on the mechanism of their action: inhibitor of protein synthesis (gentamicin, tetracycline), inhibitor of DNA synthesis (enrofloxacin) and inhibitor of synthesis of cellular wall (сeftriaxone). Previous studies revealed that 8 hours following the contact of virus and Staphylococcus, microbial cells began to undergo lysis, which decreased their number 10-fold, and 32 h after the phage started to contact the biofilm, no bacterial cells were generating at all (Horiuk et al, 2020). In this study, we determined the number of vital bacteria in 24h of biofilm of S. aureus var.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Those antibiotics were chosen depending on the mechanism of their action: inhibitor of protein synthesis (gentamicin, tetracycline), inhibitor of DNA synthesis (enrofloxacin) and inhibitor of synthesis of cellular wall (сeftriaxone). Previous studies revealed that 8 hours following the contact of virus and Staphylococcus, microbial cells began to undergo lysis, which decreased their number 10-fold, and 32 h after the phage started to contact the biofilm, no bacterial cells were generating at all (Horiuk et al, 2020). In this study, we determined the number of vital bacteria in 24h of biofilm of S. aureus var.…”
Section: Resultsmentioning
confidence: 94%
“…Earlier described Phage SAvB14 (Horiuk et al, 2020), as a specific staphylococcus bacteriophage, is efficient in destroying biofilms developed by S. aureus var. bovis in cows' mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study complements our earlier data on laboratory studies of phages of S. aureus var . bovis , including their morphology, lytic activity, and the effect of Phage SAvB14 on staphylococcal biofilms [ 3 , 6 , 26 ]. Prototypes of a drug based on Phage SAvB14 have been created, and clinical trials are underway.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing spread of antibiotic resistance among clinical isolates of Staphylococcus aureus is a major problem in human and veterinary medicine [ 1 - 3 ]. The genus Staphylococcus includes commensals and pathogens in both humans and animals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%